Powerain Carwash And Maintanance Services Sdn Bhd / Mohamad Izwan Abdul Ghani... [et al.] - Minhat, Khairul Fadzlullah; Abd Rahim, Ahmad Ashraff; Abd Ghani, Mohamad Izwan; Zakaria, Muhammad Nasrun (2001)
Powerain Carwash and Services Sdn Bhd is a private company that runs washing and maintanance services for automobile. they started their business on 1 January 2005 and their business area are located at Mergong, Alor Setar, Kedah